Information on food additives on food labels in Brazil: a critical analysis - Vanessa dos Santos Pereira Montera; Ana Paula Bortoletto Martins; Laís Amaral Mais; Daniela Silva Canella (Universidade de São Paulo, 2023)
ABSTRACT Questions about the safety of food additives and their consumption have been raised in recent years. The increased exposure to these substances, either by intake of ultra-processed foods or by the broad use and combination of various categories of additives, may be related to higher risks to consumer health. This article comments on the results of a study that quantified and characterized food additives found on the labels of 9,856 packaged foods and beverages available in Brazilian supermarkets. The study adopted a field diary method to record and analyze nonconformities in the lists of ingredients. The objective of this article is to discuss the use of additives identified on the labels and the limitations of Brazilian legislation, which should guarantee the right to information and health.